2018
DOI: 10.1080/14767058.2018.1481953
|View full text |Cite
|
Sign up to set email alerts
|

Combined Doppler ultrasound and platelet indices for prediction of preeclampsia in high-risk pregnancies

Abstract: Abnormal platelet indices combined with abnormal Doppler is a predictor of severity rather than the rate of development of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The data analysis in this study indicated that abnormal uterine Doppler indices and the presence of a notch between the 19th and 22nd weeks of gestation in normal singleton pregnancies is a risk factor of developing adverse maternal and fetal outcomes such as fetal growth restriction, SGA, severe preeclampsia, HELLP, oligohydramnios placental insufficiency and placental abruption. These findings are compatible with previous studies of uterine arteries Doppler screening and the combined screening including maternal characteristics and history (3,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Although the identification of high-risk pregnancies in the second trimester could not yet improve maternal and fetal morbidity and mortality as demonstrated in several studies in the past 20 years, the administration of a daily low dose of aspirin starting before the 16th week of gestation has shown significant reduction in the prevalence of these complications (3,11,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 90%
“…The data analysis in this study indicated that abnormal uterine Doppler indices and the presence of a notch between the 19th and 22nd weeks of gestation in normal singleton pregnancies is a risk factor of developing adverse maternal and fetal outcomes such as fetal growth restriction, SGA, severe preeclampsia, HELLP, oligohydramnios placental insufficiency and placental abruption. These findings are compatible with previous studies of uterine arteries Doppler screening and the combined screening including maternal characteristics and history (3,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Although the identification of high-risk pregnancies in the second trimester could not yet improve maternal and fetal morbidity and mortality as demonstrated in several studies in the past 20 years, the administration of a daily low dose of aspirin starting before the 16th week of gestation has shown significant reduction in the prevalence of these complications (3,11,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 90%
“…Doppler was used to report the accumulation of platelets radiolabelled with 111‐indium in atherogenic arteries in patients with cerebral ischemia 25 . Abnormal platelet index combined with high pulsatility index and resistance index values in Doppler analysis results in a higher incidence of severe preeclampsia 26 . Thus, the platelets may interact with the endothelium leading to endothelial dysfunction; however, the mechanisms involved in this interaction are unknown.…”
Section: Endothelial Dysfunction In Gdmmentioning
confidence: 99%
“…These authors confirmed conclusion of previously mentioned study, and showed that analysis of maternal factors, uterine artery PI by Doppler, mean arterial pressure and serum placental growth factor (PLGF) enabled prediction over 90% of preeclampsia. Abdel Razik and colleagues investigated the interconnection between Doppler ultrasound parameters: diastolic notch, PI and RI, and platelet indices: platelet count (PC), mean platelet volume (MPV), platelet distribution width (PDW) and platelet large cell ratio (Plcr) (24). They analyzed 270 normal pregnant women between 20 th and 24 th week of gestation and showed that patients with preeclampsia had higher frequency of diastolic notching, as well as higher PI and RI, combined with significant increase of MPV and PDW.…”
Section: Uterine Artery Doppler In Preeclampsia Predictionmentioning
confidence: 99%